2015
DOI: 10.4049/jimmunol.1500322
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Teleost Skin CD8α+ Dendritic-like Cells, Representing a Potential Common Ancestor for Mammalian Cross-Presenting Dendritic Cells

Abstract: Although fish constitute the most ancient animal group in which an acquired immune system is present, the presence of dendritic cells (DCs) in teleosts has been addressed only briefly, and the identification of a specific DC subset in teleosts remained elusive because of the lack of specific Abs. In mice, DCs expressing CD8α+ in lymphoid tissues have the capacity to cross-present extracellular Ags to T cells through MHC I, similarly to tissue-derived CD103+ DCs and the human CD141+ DC population. In the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
70
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 62 publications
9
70
0
Order By: Relevance
“…We found very low levels of expression of CD141 in systemic (HK) and nasal CD8 + T cells but high expression in gut CD8 + cells. Our results are in agreement with a previous study that showed low CD141 expression in trout splenic CD8 + T cells (32). With regards to the high CD103 and CD141 expression in gut, it is worth mentioning that teleost and mammalian DCs can also express CD103 and CD141 (32, 6769) and therefore the presence of few CD8 + /DC-SIGN−/CD103 + /CD141 + DCs or DC progenitors in the gut CD8α + cell population, although unlikely, cannot be ruled out.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…We found very low levels of expression of CD141 in systemic (HK) and nasal CD8 + T cells but high expression in gut CD8 + cells. Our results are in agreement with a previous study that showed low CD141 expression in trout splenic CD8 + T cells (32). With regards to the high CD103 and CD141 expression in gut, it is worth mentioning that teleost and mammalian DCs can also express CD103 and CD141 (32, 6769) and therefore the presence of few CD8 + /DC-SIGN−/CD103 + /CD141 + DCs or DC progenitors in the gut CD8α + cell population, although unlikely, cannot be ruled out.…”
Section: Discussionsupporting
confidence: 94%
“…Previously, CD103 and integrin β7 were shown to be abundantly expressed in thymic and mucosal (gill and gut) trout CD8α + lymphocytes (31). Moreover, unlike their mucosal counterparts, trout splenic CD8 + T cells do not express CD103 (32). Here we show that trout nasal CD8α + lymphocytes have a significantly lower expression of CD103 but much higher expression of integrin β2 than gut CD8α + lymphocytes.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…rCK12a treated and i.p. rCK12a treated (n = 3) rainbow trout were stained with anti-trout CD8α + and MHC-II antibody as explained elsewhere (29, 61, 62). Nuclei were stained with DAPI DNA stain and slides were observed under a Nikon Ti fluorescence microscope.…”
Section: Methodsmentioning
confidence: 99%